Penyuluhan Dan Edukasi Tentang Penyakit Diabetes Mellitus - Nurjani, Nurjani; Lupita , Candra; Rohimah , Hani Katu; Valenthine , Dewi Lara; Larina , Ceni Ade Rosa; Janeri , Brian; Sari , Lezi Yovita; Rohani , Tuti; Azissah , Danur (Jurnal Kewirausahaan dan Bisnis, 2025)
Type 2 diabetes mellitus is a non-communicable disease often caused by poor dietary habits and lack of physical activity. Irregular eating patterns and physical inactivity need to be addressed to help patients maintain their blood sugar levels. This study aims to examine the relationship between diet, physical activity, and blood sugar levels in patients with type 2 diabetes mellitus at the Kampung Delima Health Center.Diabetes mellitus is a metabolic disorder characterized by elevated blood sugar levels due to problems with the insulin hormone, which helps maintain the body's balance by lowering blood sugar levels (American Diabetes Association, 2017). This disease is heavily influenced by lifestyle, so daily activities such as eating, sleeping, and working must be balanced. The amount and type of food, as well as exercise, need to be carefully managed and should not be neglected. Diabetes mellitus patients must pay attention to their diet, including calorie intake, necessary nutrients, types of food, and regular meal schedules (Sulistyowati, 2017), which describes the types and quantities of food consumed daily.This community service activity was conducted from January 20, 2025, to January 31, 2025. The evaluation of the activity included education on healthy lifestyle habits to reduce the risk of developing diabetes mellitus, aiming to provide advice and education to the community about diabetes mellitus.